Experiences of health information-seeking behaviour in preoperative patients with lung cancer: a qualitative study in China - Wei Li; Lihua Huang; Jie Zhu; Jiayi Guo; Man Ye (BMJ Open)
Objective Surgery represents the primary therapeutic modality for lung cancer, typically administered promptly following diagnosis. Accessing pertinent information and making well-informed decisions are imperative to navigate this challenging stage. This study aimed to explore preoperative lung cancer patients’ experiences related to health information-seeking process, based on the information and methodological characteristics of health information-seeking behaviour (HISB).Design The study used a qualitative descriptive design, adhering to the Consolidated Criteria for Reporting Qualitative Research guidelines. 23 participants were purposively selected for semistructured interviews. Data analysis was conducted using inductive conventional content analysis.Setting The study was conducted in the thoracic surgery ward of a tertiary hospital located in China.Participants A total of 23 participants, consisting of 12 males and 11 females, were recruited. Eligible participants were patients with lung cancer aged 18 and above, capable of articulate expression, informed about their diagnosis, preparing for surgical intervention and willing to engage voluntarily in the study.Results Four main categories were identified. Participants exhibited different psychological coping strategies and personalised health information needs in their information-seeking behaviour. Challenges emerged in comprehending and assessing factors related to lung cancer, treatment alternatives, surgical complications, online media resources and preoperative exercise protocols. The importance of preoperative respiratory training was often underestimated. Additionally, some participants displayed a tendency to passively receive information, thereby impeding their ability to effectively self-manage throughout the perioperative stage.Conclusions Understanding the experiences in HISB is crucial for improving the health outcomes of patients with lung cancer. Healthcare providers should adopt a patient-centred approach to health education, with a targeted effort to recognise and mitigate specific barriers in clinical practice. Further research is needed to explore effective strategies aimed at augmenting health information-seeking process among patients with lung cancer before surgery.